The Use Of Video To Improve The Speaking Skill Of The First Semester Students Of Pgmi Program Of Hamzanwadi Islamic Institute (Iaih) NW AT Pancor - syamsul rizal; Azhari Fathurrohman (Fakultas Tarbiyah Institut Agama Islam Hamzanwadi NW Pancor, 2020)
The teaching of English as a Foreign Language (EFL) speaking is necessary for university students to have basic skills of oral communication. Using teaching media in the teaching of EFL speaking might be beneficial to help students improve their speaking skills. As teaching media, video can offer audio and visual model of target language as complete stimuli. The aim of this research was to investigate the use of video as teaching media to improve the speaking skill of the first semester students of PGMI program of IAIH NW at Pancor. Based on the data of preliminary study, it was found that the students encountered many problems in their speaking class such as; the students had low motivation and reticence to speak, poor grammar and vocabulary, and had some errors in pronunciation. With regard to the problem, this classroom action research was conducted to solve those problems occurring in the speaking class. This research was a collaborative action research in which a collaborator assisted the researcher to collect the data using speaking scoring rubric, questionnaire and field notes. This research was conducted in two cycles focusing on the improvement of the students’ speaking performance and their positive attitude to the implementation of the use of video as teaching media in the speaking class. After the implementation of the use of video as teaching media in the speaking class for two cycles, it revealed that the use of video could improve the students’ speaking performance and give them positive attitude to the implementation activities. The findings showed that the average score of the students’ speaking performance could achieve 85.11 from the determined score 75. In addition, it was also found that 84.13 % of the students had positive attitude to the implementation of the use of video in the speaking class. The implementation of the use of video as teaching media in speaking class can cover a procedure of three main phases: The first phase is pre-viewing, the second phase is whilst-viewing, and the third phase is post-viewing. Based on the findings, it is concluded that the use of video as teaching media can be one of the solutions to improve not only the students’ speaking skills but also the their’ positive attitude in the teaching of speaking. Therefore, English teachers are suggested to use the video as teaching media to teach their students in speaking class and it is also possible to teach other language skills or components.